Weed Control in Beets - William M. Stall (EDIS, 2006)
Revised! HS-951, a 2-page fact sheet by William M. Stall, provides a table of listing herbicides available to growers for chemical weed control of beets. This publication updates the 2003 tables to reflect current recommendations. Published by the UF Department of Horticultural Sciences, October 2006.